Distribuição de Amazilia (Aves: Trochilidae) no nordeste oriental do Brasil - Santana, Lucas de Lima Seixas (2015)
Biogeographic studies try to understand the distribution patterns of the biologic groups, considering historic and biologic factors. At Brazil’s Northwest, there are few studies in this sphere. In this area, there are three species of hummingbirds: A. leucogaster, A. versicolor and A. fimbriata, wich have a genetic proximity – belong to the same gender – and are sympatric, and because of that can turn out to be potential competitors and don’t co-occur. But in case they do co-occur, they can be syntopic due to a divergence in some niche dimension. In order to comprehend wich historic and ecologic factors mold the distribution of these species, we reviewed the occurrences of the three of them, analized potencial distribution based on the niche aspects and revised the phylogenies of the group. Therefore, we used QGis 2.9, R 3.0.1 (Maxent), bioclimatic variables of the WorldClim, Statistic 7.0 (ANOVA one way) and the recently published phylogenies. We’ve registered 232 points of occurrence, (94%) of the points are associated to forest areas, and only 15 (6%) occurred in open environments. The co-occurrence between A. leucogaster and A. fimbriata can be easily explained by the phylogenetic distance and by the niche divergence, once they were the species with the most different data when observed by these factors. There is no sympatry of A. leucogaster and A. versicolor. The performances of the models and test of the ANOVA indicate that A. fimbriata and A. versicolor show themselves more similar in the fundamental niche, while the A. leucogaster niche is influenced in a differentiated way by the variables. A. leucogaster, the most recent of the three, has the history of lineage linked to environments of the Quaternário, related to the coastal forests. A. versicolor have a history based on the expansion of humid forests of the Mioceno Superior and Plioceno. When it comes to the A. fimbriata, it has a history that goes from the Mioceno Superior to the Pleistoceno Médio, also related to the expansion of the forests. Because Amazilia is not a monophyletic group and A. fimbriata presents ecologic and historic data that represent an evolutive divergence, we sugest a different taxonomic representation, at the gender level, to this species.